Analysis of the Status of Building Density in Plans of Urban Development in Tabriz - Rasul Gorbani; Firuz Jafari (نشریه جغرافیا و برنامه‌ریزی, 2015)
Abstract Building density as the total floor area ratio of all storeys used for residential purposes is an important issue in urban planning and land management. Today, because of the lack of resource and to decrease urban development costs and to provide goods and commercial services attention toward the increment of to more dense and increasing building density has increased. This article reviews the concept of building density and documents and regulations approved on this subject during recent years in Tabriz. It is a descriptive-analytic research. The increasing of building density in cities with growing populations is one of the strategies approved for controlling extension and balance of urban space. Increasing density in cities without attention to balances and equilibrium might cause problems and solving that will take much time, energy and would require higher costly. Studies show that among the regulations approved for comprehensive plans and regulations in the detailed plans and projects, there is an obvious difference. For instance, open space reduction rule was approved in master plan to be 55 m2 upto 10 m2 in detailed plan of Tabriz. Obviously, if in the process of determining the building density measures such as occupied building, height, proportion of mass and space, and residential neighborhoods carrying capacity are considered, it ciykd have helped achieve a coherent and systematic space for the city and add to the quality of urban spaces continuously.